Bromo- and chloro-substituted flavones induce apoptosis and modulate cell death pathways in canine lymphoma and leukemia cells - a comparative in vitro study - Dudek, Anita; Dejnaka, Ewa; Sulecka-Zadka, Joanna; Perz, Martyna; Krawczyk-Łebek, Agnieszka; Kostrzewa-Susłow, Edyta; Pruchnik, Hanna; Pawlak, Aleksandra (Frontiers in Molecular Biosciences, 2026)
IntroductionAlthough flavonoids are natural compounds with anti-cancer potential, their clinical application is limited due to the low bioavailability. Structural modification, such as halogenation, has been identified as a strategy to enhance drug-like properties. The rationale behind this is that halogen substituents can increase lipophilicity, alter electronic distribution, and improve interactions with cellular targets. Here, we investigated the cytotoxic mechanisms of three halogenated flavones - 4′-chloroflavone (Cl-F), 6,8-dichloroflavone (DiCl-F), and 8-bromo-6-chloroflavone (BrCl-F) - in two canine B-cell models, CLB70 (leukemia) and CLBL-1 (lymphoma), chosen for their translational relevance to human hematological cancers.MethodsCytotoxicity was assessed by MTT assay, apoptosis by annexin V/PI staining, Bcl-2 and Bcl-XL expression by Western blotting, cell cycle distribution by flow cytometry, and DNA damage by changes in H2AX phosphorylation.ResultsBrCl-F demonstrated the strongest cytotoxic activity, significantly reducing metabolic activity and increasing the proportion of apoptotic cells in both cell lines. In CLB70 cells, BrCl-F treatment was accompanied by decreased expression of Bcl-2 and Bcl-XL. DiCl-F showed moderate cytotoxicity but induced a marked increase in γH2AX levels and accumulation of cells in the G2/M phase. Cl-F exhibited weaker effects and reduced cell viability primarily at higher concentrations.ConclusionHalogenated flavones display distinct cytotoxic profiles in canine B-cell leukemia and lymphoma models, with BrCl-F showing the highest anticancer activity. These findings support further investigation of halogenated flavones as potential anticancer agents in comparative oncology.